Isolation and Immortalization of Patient-derived Cell Lines from Muscle Biopsy for Disease Modeling - Robin, Jerome D. (J Vis Exp, 2015)
The generation of patient-specific cell lines represents an invaluable tool for diagnostic or translational research, and these cells can be collected from skin or muscle biopsy tissue available during the patient’s diagnostic workup. In this protocol, we describe a technique for live cell isolation from small amounts of muscle or skin tissue for primary cell culture. Additionally, we provide a technique for the immortalization of myogenic cell lines and fibroblast cell lines from primary cells. Once cell lines are immortalized, substantial expansion of patient-derived cells can be achieved. Immortalized cells are amenable to many downstream applications, including drug screening and in vitro correction of the genetic mutation. Altogether, these protocols provide a reliable tool to generate and preserve patient-derived cells for downstream applications.